Improving the competence of heavy machinery maintenance for the community of Loa Janan Ilir District, Samarinda - Hidayat Hidayat; Darma Aviva; Abdul Halik (Universitas Muhammadiyah Magelang, 2022)
East Kalimantan is a province rich in natural resources, particularly in the mining sector, which includes coal, oil, and gas. Moreover, the mining industry is expanding at a faster rate, which is being accompanied by an increase in the demand for heavy machinery. As a result, knowing how to maintain a heavy machinery unit before operating it is critical for a dependable heavy machinery unit operator. In the community of Harapan Baru Village, Loa Janan Ilir District, Samarinda, the solution to the problem of human resource quality is to conduct training in the context of increasing competence in the field of heavy machinery unit maintenance. As a result of this program, members of the Harapan Baru Village Community Empowerment Institute now have basic knowledge of how to maintain heavy machinery units that can be used to contribute to the IKN development, which is a strategic plan of the Indonesian government.